Tshe dpag med źi ba lha maṅ gi cho ga ʼchi med ʼdod paʼi re skoṅ nag ʼgros su bkod pa bźugs so - Padma-dkar-po, ʼBrug-chen IV, 1527-1592 (s.n., 1968)
Ritual for the propitiation of the quiescent deities of the Amitāyus Cycle arranged for convenient liturgical recitation.